Clinical characteristic and therapy results of presumed ocular tuberculosis and their relation to HIV status (Faculty of Medicine Universitas Indonesia, 2012)
Background: Ocular tuberculosis (TB) emerges as an important cause of intraocular inflammation, partly due to the increasing number of HIV/AIDS patients. This study attempts to identify ocular signs that are associated with ocular TB and assess the efficacy of the treatment and their relation to HIV status. Methods: Medical records of all 56 patients diagnosed with presumed ocular TB in Cipto Mangunkusumo Hospital between January 2006 and December 2011 were reviewed. Demographic and clinical characteristics and HIV status were recorded as well as efficacy of treatments given. Results: There were 39 patients included with mean age 35.38 ± 13.1 and male to female ratio was 2:1. Unilateral involvement was in 26 (66.7%) patients. From all, four (10.3%) had anterior uveitis, 14 (35.9%) posterior uveitis, 21 (53.8%) panuveitis, and none had intermediate uveitis. Most of them (32/82.1%) have concurrent other organ TB. Five out of 8 (62.5%) HIV positive patients had granulomatous inflammation and 3 (37.5%) had non-granulomatous inflammation and all eight of them had concurrent other organ TB. The other 7 known non-HIV patients, six (85.7%) have non-granulomatous inflammation. Treatment with anti-tubercular therapy (ATT), combination ATT and steroid or steroid alone increased visual acuity. However steroid alone was slightly have more frequent recurrences (1.4 ± 0.89 episodes of inflammation). Conclusion: Ocular TB in our study had variable clinical manifestations and ocular inflammation was predominantly non-granulomatous in HIV negative patients and granulomatous in HIV infected patients. All HIV positive patients the ocular TB was always accompanied by manifestations in other organs. The treatment with steroids solely resulted in improved vision but was characterized by frequent recurrences. (Med J Indones. 2012;21:214-9)